A Discourse Analysis Of Students' Metaphorical Language Comprehension In Interpretative Listening At The English Education Study Program Of Universitas Nias - Elwin P. Zebua (Academy of Education Journal, 2026)
Interpretative listening asks learners to move beyond decoding surface acoustic input and to reconstruct meaning that a speaker leaves implicit, a demand that intensifies considerably when spoken discourse is organised around metaphor. This study offers a discourse-analytic account of the recurrent errors that second-semester students of the English Education Study Program at Universitas Nias (UNIAS) produce when inferring implicated, non-literal meaning during interpretative listening. Framed within a qualitative descriptive design (Creswell and Poth, 2018), the study was conducted from March to May 2026 with the entire cohort of 43 second-semester students enrolled in the 2025/2026 academic year, engaged through total sampling. Three complementary instruments generated the data set: a Listening Comprehension Worksheet cross-referenced with an Audio Transcript Matrix, Think-Aloud Protocols (TAPs) capturing real-time inferential reasoning, and a Semi-Structured Interview Guide eliciting retrospective metacognitive reflection. The three data sets were analysed through discourse-analytic coding informed by relevance-theoretic and conceptual-metaphor perspectives, and triangulated across instruments to strengthen credibility. Six recurrent categories of inferencing error emerged: literal-meaning fixation, source-domain mismapping, discourse-context neglect, prosodic and paralinguistic cue oversight, first-language schema overgeneralisation, and processing-load-induced shallow inferencing. These patterns are traced to learners' as yet underdeveloped capacity to construct the ad hoc, context-adjusted concepts that relevance theory holds to be central to metaphor resolution, compounded by conceptual-metaphor schemas transferred from Indonesian and Nias. The study closes with a proposal to embed explicit metaphor-awareness instruction and reflective, TAP-based listening tasks into the Course Learning Outcomes of interpretative listening subjects under the Outcome-Based Education (OBE) curriculum, so that listening pedagogy is more closely aligned with the inferential demands of authentic spoken discourse.